2010
DOI: 10.1118/1.3453576
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of patient specific IMRT QC to systematic MLC leaf bank offset errors

Abstract: None of the techniques or criteria tested is sufficiently sensitive, with the population of IMRT fields, to detect a systematic MLC offset at a clinically significant level on an individual field. Patient specific QC cannot, therefore, substitute for routine QC of the MLC itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 9 publications
0
31
0
1
Order By: Relevance
“…Rangel et al 53 pointed out that patient-specific IMRT QA cannot replace routine MLC QA as none of their IMRT QA criteria tested were sufficiently sensitive to identify MLC offsets within a tolerance of 0.3 mm on a single field basis. MLC log files have been used previously to quantify leaf positional errors for IMRT 54,55 as well as RapidArc.…”
Section: Discussionmentioning
confidence: 99%
“…Rangel et al 53 pointed out that patient-specific IMRT QA cannot replace routine MLC QA as none of their IMRT QA criteria tested were sufficiently sensitive to identify MLC offsets within a tolerance of 0.3 mm on a single field basis. MLC log files have been used previously to quantify leaf positional errors for IMRT 54,55 as well as RapidArc.…”
Section: Discussionmentioning
confidence: 99%
“…The detection sensitivity of MLC leaf positioning shifts has been studied with different devices 18, 19, 20, 21, 22. Yan et al 18.…”
Section: Discussionmentioning
confidence: 99%
“…showed systematic outward MLC gap width shifts up to 2 mm could not be detected with ArcCHECK diode array using Gamma criterion 3%/2 mm for true composite dose analysis of both prostate and head and neck treatment, whereas an absolute dose measurement with the criterion of 2% at isocenter using an inserted micro‐ionization chamber was able to identify 1 mm MLC gap shifts. Rangel et al 20. reported the criteria most sensitive to detect the MLC leaf shifts were 3% absolute dose difference, 3 mm DTA for MapCHECK, the Gamma index with 2%/2 mm for the EPID.…”
Section: Discussionmentioning
confidence: 99%
“…A number of groups have categorized the impact of these types of MLC errors in IMRT and VMAT for a range of treatment sites. (4,17–21) Rangel et al (18) found that an MLC gap error of 1 mm resulted in a systematic dose difference of 2.7% and 5.6% for prostate and head and neck IMRT respectively. Other groups have reported that a systematic MLC gap error of 1 mm can introduce dose errors of up to 10% in IMRT treatments (21) .…”
Section: Introductionmentioning
confidence: 99%